Optimalisasi Infrastruktur Industri untuk Meningkatkan Produktivitas dan Daya Saing UMKM di Desa Wangandowo - Haya, Aina Fathia; Rohmah, Farida (Advances In Social Humanities Research, 2024)
The community is expected to be able to understand the opportunities that exist in the surrounding area in order to maximize local economic growth. As an example, the author cites the development of industrial infrastructure in Wangandowo Village, Bojong, Pekalongan Regency. This industrial development project can create great opportunities for the general public, which can be utilized to set up businesses to improve their quality of life. This is the focus of the researcher's analysis to explore this phenomenon, especially related to the challenges faced by students or entrepreneurs in the MSME (Micro, Small and Medium Enterprises) sector which is an obstacle in the industrial development sector mentioned above. project. The research method used is a qualitative research method followed by interpretation through observation techniques and theoretical basis. By using the basis of Phenomenology, participants can take risks in exploiting existing business opportunities. In addition, participants must have patience, consistency, be able to adapt, and other important things implemented by existing local olekoman and be successful in pursuing their field as entrepreneurs. One of the limitations of this research is the small number of participants so it is unable to fully capture the broader phenomenon. This can serve as a guide for future researchers to expand their understanding of local economic phenomena and potential.